2020
DOI: 10.1515/jpem-2020-0273
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric indices and cardiometabolic risk factors in a Ghanaian adolescent population

Abstract: ObjectivesAdolescent overweight and obesity is a public health concern globally, especially in lower- and middle- income countries where there is an additional burden of undernutrition. The prevalence of adolescent overweight/2obesity has increased markedly over the past three decades. The transition in dietary habits coupled with reduced physical activity has been blamed for the increasing trend. Overweight/obesity in adolescence is complicated by cardiometabolic, respiratory, musculoskeletal and psychosocial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Another (Ganle et al, 2019) found that children (5-16 year-olds) who consumed fizzy drinks on most days had statistically significant increased odds of being obese compared to children who hardly or did not consume any fizzy drinks at all. Another study (Sirikyi et al, 2021) found that ice cream intake was predictive of overweight/obesity but did not find significant Darling et al (2020) association between fast food intake and sweetened beverages intake and BMI categories.…”
Section: Findings At Micro-levelmentioning
confidence: 94%
See 2 more Smart Citations
“…Another (Ganle et al, 2019) found that children (5-16 year-olds) who consumed fizzy drinks on most days had statistically significant increased odds of being obese compared to children who hardly or did not consume any fizzy drinks at all. Another study (Sirikyi et al, 2021) found that ice cream intake was predictive of overweight/obesity but did not find significant Darling et al (2020) association between fast food intake and sweetened beverages intake and BMI categories.…”
Section: Findings At Micro-levelmentioning
confidence: 94%
“…The sample sizes used in the studies vary. In one case, a study that looked at food consumption in orphanages included only 40 participants purposively sampled (Sadik, 2010), while another study included all first-year students (196) who reported for medical test at a university in the Cape Coast region (Sirikyi et al, 2021). Other studies had much larger sample sizes.…”
Section: Tools Methods Metrics and Geographies Commonly Adopted In An...mentioning
confidence: 99%
See 1 more Smart Citation